A Morphometric Analysis of Hamate Autograft for Proximal Scaphoid Reconstruction - Thayer, Mary Kate; Bluth, Benjamin; Huang, Jerry I. (Journal of Wrist Surgery, 2021)
Objective Recently, authors have investigated using the proximal hamate as osteochondral autograft for proximal pole scaphoid reconstruction in the case of nonunion with avascular necrosis. The aim of our study was to analyze the morphology and anatomic fit of the proximal hamate compared with the proximal pole of the scaphoid using cadaveric specimens.Materials and Methods Ten cadaver specimens (five males and five females) were dissected. Scaphoid and proximal hamate bones were measured by two independent investigators using electronic calipers and radius of curvature gauges. After measurements were determined to have good correlation, the average value of the two observers' measurements were used for further analysis. Sagittal radius of curvature (ROC), coronal ROC, depth, width, and maximum graft length were compared.Results The average depth of the scaphoid proximal pole was 12.3 mm (standard deviation [SD] = 1.12) compared with 11.3 mm (SD = 1.24) for the proximal hamate (p = 0.36). The average width was 7.8 mm (SD = 1.00) in the scaphoids compared with 8.6 (SD = 1.05) in the hamates (p = 0.09). There was also no significant difference in the sagittal ROC between hamates (9.1 mm, SD = 1.13) and scaphoids (9.5 mm, SD = 0.84; p = 0.36). All of these average measurements were within 1 mm. There was a significant difference between the coronal ROC of the hamate (23.4 mm) and scaphoid (21.1 mm) bones in our samples (p = 0.03). Females were on average smaller than their males, but there was no significant difference in fit based on sex alone.Conclusion The proximal pole of the hamate has similar morphology and size as the scaphoid, with similar depth, width, and sagittal ROC. It has potential as an osteochondral autograft for proximal pole scaphoid reconstruction.
Keywords: autograft; hamate; nonunion; scaphoid; osteochondral graft